Contagion comeback: unravelling the measles outbreak across the USA - Tahir, Iman Muhammad; Kumar, Vijay; Faisal, Hanya; Gill, Anosh; Kumari, Vineeta; Tahir, Haya Muhammad; Haque, Md Ariful (Frontiers in Public Health, 2024)
Measles, a highly contagious respiratory illness caused by the measles virus (MeV), poses significant global and national public health challenges despite advancements in vaccination efforts. Though measles was declared eliminated in the United States in 2000, recent years have seen a resurgence of cases, particularly in under-vaccinated communities. This resurgence is compounded by factors such as vaccine hesitancy, the impact of the COVID-19 pandemic on immunization rates, and international travel introducing new cases from endemic regions. This paper examines the epidemiology and recent measles outbreaks in the United States, focusing on the significant rise in cases from 2020 to 2024. The analysis highlights the importance of maintaining high vaccination coverage, particularly in vulnerable populations, and explores the challenges of managing outbreaks. The study also reviews the pathophysiology, clinical presentation, diagnosis, and treatment of measles, emphasizing the role of prevention and control measures, including the MMR vaccine, public health interventions, and international cooperation in addressing this persistent threat.